Vertical Coordination in the Meat Supply Chain - The Effects of (Unlabeled) Private Standards for Animal Welfare - Julia Hoḧler; Rainer Kuḧl (German Journal of Agricultural Economics (GJAE), 2017)
Animal welfare is increasingly relevant in the public debate. As a reaction, German companies and associations in the farming, meat and retail sector intervened in the market for meat and founded an animal welfare initiative. Farmers are compensated for implemented animal welfare measures with money which is funded by retailers. The resulting meat is not labeled and thus not distinguishable from conventional meat. In our model, we show the relative merits of the initiative especially from a retailer's point of view as compared to the introduction of labeled meat produced under restrictive practices. We combine our results with considerations on the distribution of market power and the degree of vertical coordination along the value chain for meat.
Keywords: 330